2003
DOI: 10.1016/s0736-0266(03)00114-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying thumb rotation during circumduction utilizing a video technique

Abstract: Thumb rotation is an essential component of circumduction in order to achieve pulp to pulp contact. In order to evaluate opponensplasty, a device was developed to quantify thumb rotation utilizing a special jig to hold the hand and video analysis. Twenty-seven healthy volunteers (12 female and 15 male) were tested to obtain normative data. Thumb rotation was measured as the difference in angle between the thumb in abduction and extension and maximal circumduction. Rotation angles varied from 70" to 110". No ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 21 publications
(28 reference statements)
2
33
0
1
Order By: Relevance
“…The circumduction rotation of the thumb is the movement required to alternate between a lateral grasp and a power or precision grasp. An analysis of human hand kinematics shows an average circumduction motion of 90.2°, which is achieved through a combination of three joints at the base of the thumb [40]. As can be seen in Tables 2 and 9, the circumduction axis of current hands is not always oriented parallel with the wrist rotation axis.…”
Section: Thumb Kinematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The circumduction rotation of the thumb is the movement required to alternate between a lateral grasp and a power or precision grasp. An analysis of human hand kinematics shows an average circumduction motion of 90.2°, which is achieved through a combination of three joints at the base of the thumb [40]. As can be seen in Tables 2 and 9, the circumduction axis of current hands is not always oriented parallel with the wrist rotation axis.…”
Section: Thumb Kinematicsmentioning
confidence: 99%
“…The coupling can also help the timing of the grasp if all of the fingers are actuated simultaneously. Further discussion of the role of the thumb circumduction axis can be found in other reviews [1,21,23,40].…”
Section: Thumb Kinematicsmentioning
confidence: 99%
“…Thus, the functional joint axes should correspond to joint variable sequences with small variation of θ 2 values. The second aspect is that the FE RoM is generally larger than the AA RoM for unimpaired CMC joints [5], [6]. Finally, the FE axis fixed in the hand frame is proximal to the AA axis fixed in the thumb metacarpal frame due to the saddle joint geometry between the metacarpal and trapezium bones [3], [4], [11], [13].…”
Section: Optimization Cost Metricmentioning
confidence: 99%
“…Cooney et al [5] also determined the orientation of in vitro CMC axes from the ridges of the trapezium bone surface in cadaver hands, and these results reported with respect to the hand dorsum provide a single constant model of the axis orientations to subsequently measure in vivo CMC mobility. Noninvasive techniques proposed by Coert et al [6] and Zhang et al [7] evaluate thumb circumduction based on the observed motion of the thumb segments, without determining a kinematic model for the CMC axes. In contrast, Chèze et al [8] and Cerveri et al [9] have developed techniques for estimation of the in vivo CMC axes from isolated thumb movements such as circumduction and flexion-extension (FE).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, noninvasive, marker-based video methods have been used to study advanced kinematic features thus providing a more accurate representation of thumb motion. 2,[8][9][10][11] Marker-based motion analyses were applied to study thumb pathokinematics in individuals with cervical myelopathy 12 and lower median nerve block; 13 the authors reported aberrant thumb kinematics during pinch movements.…”
mentioning
confidence: 99%